HIV in the Penitentiary System of the Region with High Level of Prevalence of HIV-infection over a Period of Years (on the Example of Tyumen Region) - S. Ye. Kondratova; A. N. Marchenko; E. A. Kashuba; A. A. Bel'tikova; O. A. Nesterova (Эпидемиология и вакцинопрофилактика, 2019)
Relevance.  HIV infection has a negative impact on the demographic and economic situation. Despite the slowdown in prevalence, incidence and prevalence rates remain. Aim. Analysis of the development of the HIV epidemic process in the risk group of prisoners ofthe Tyumen region over a period of many years. Materials and methods.  The work used statistical data from the Center for the Fight against AIDS of the Tyumen Oblast State Budgetary Health Institution, the Office of the Federal Service for Supervision of Human Welfare in the Tyumen Region. The work uses analytical, epidemiological methods, research methods, statistical evaluation methods, average errors, average errors, estimated significance, differences between comparison factors. Results. In the region, HIV-infection affects more than 1% of the population. The group of prisoners occupies a leading position Prisoners in prisons are at increased risk of infection  in the structure of HIV-infected  region with an average multiyear share of 16.3%. The maximum rate of increase in HIV among prisoners was + 44.0%, the minimum – -27.0%. The average long-term  share of nonresident prisoners was 40.6 ± 0.65%, and among those registered in the region – 59.4 ± 0.65%. Places of deprivation of liberty must be considered as one of the main places with a high degree of probability of contracting HIV due to the contact of a healthy population with HIV infected, like in no other location. Conclusions. In 2001, the share of prisoners of all identified HIV – positive in the region amounted to 30.3%. The nature of the generalized course of HIV infection has acquired in prisons since 2005. The intensity of the HIV epidemic process in the region is supported, among other things, by the continuity of the formed connection between the special contingent and the law-abiding population, which requires targeted attention from the sanitary and preventive services.